Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1080/22221751.2023.2211685
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal enhancement of SARS-CoV-2 and influenza virus replication in human pluripotent stem cell-derived lung organoids

Abstract: Patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A virus (FLUAV) coinfections were associated with severe respiratory failure and more deaths. Here, we developed a model for studying SARS-CoV-2 and FLUAV coinfection using human pluripotent stem cell-induced alveolar type II organoids (hiAT2). hiAT2 organoids were susceptible to infection by both viruses and had features of severe lung damage. A single virus markedly enhanced the susceptibility to other virus infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This mode of promotion manifested as enhanced ACE2 receptor expression. 126,127 The data demonstrated that the mRNA levels of ACE2 receptors in host cells increased by 2-3 times after infection with influenza and by 28 times in cases of coinfection with influenza and SARS-CoV-2. 127 But other studies suggest otherwise.…”
Section: Harms Of Sars-cov-2 Coexisting With Influenzamentioning
confidence: 95%
“…This mode of promotion manifested as enhanced ACE2 receptor expression. 126,127 The data demonstrated that the mRNA levels of ACE2 receptors in host cells increased by 2-3 times after infection with influenza and by 28 times in cases of coinfection with influenza and SARS-CoV-2. 127 But other studies suggest otherwise.…”
Section: Harms Of Sars-cov-2 Coexisting With Influenzamentioning
confidence: 95%
“…Therefore, the use of lung organoids, e.g., derived from human pluripotent stem cells, provides a model with multiple cell types, which offers a system that recapitulates key aspects of the lung physiology critical to studying the mechanisms and effects of respiratory viral coinfections and potential therapeutic molecules [ 93 ]. Although lung organoids are not without experimental limitations, they have been used to study the molecular mechanisms underlying enhanced disease with the coinfection of IAV and SARS-CoV-2 [ 94 ]. Future research, however, is needed to improve this in vitro system and overcome the technical limitations of viral inoculation in lung organoids.…”
Section: Experimental Model For Studying Respiratory Viral Coinfectionsmentioning
confidence: 99%
“…Similarly, influenza A virus, a highly transmissible respiratory virus responsible for seasonal epidemics and occasional pandemics, has been the subject of organoid-based studies. 157 , 164 , 165 Infection of influenza A virus begins when its hemagglutinin binds to sialic acid of membrane receptors of host cells. 182 Zhou et al 164 constructed human airway organoids with enhanced proximal differentiation, promoting the expression of ciliated cells.…”
Section: Respiratory Infection Modelingmentioning
confidence: 99%